Reference Standards for Nerve Conduction Studies of Individual Nerves of Lower Extremity With Expanded Uncertainty in Healthy Korean Adults - Jae Yoon Kim; Eunkyung Kim; Hyung Seok Shim; Jae Hyun Lee; Goo Joo Lee; Keewon Kim; Jae-Young Lim; Jaewon Beom; Sang Yoon Lee; Shi-Uk Lee; Sun Gun Chung; Byung-Mo Oh (Annals of Rehabilitation Medicine, 2022)
Objective To develop a set of reference standards for tibial motor, common peroneal motor, sural sensory, and superficial peroneal sensory nerve conduction studies (NCSs) with expanded uncertainty in a healthy Korean population. Methods Standardized procedures were conducted for individual lower extremity NCSs of 199 healthy participants in their 20s (n=100) and 50s (n=99). Mean values and expanded uncertainties for parameters were analyzed with thorough consideration of multiple uncertainty factors under the International Guide to the Expression of Uncertainty in Measurement. In addition, side-to-side differences in onset latency, amplitude, and nerve conduction velocity (NCV) were analyzed. Results Mean (reference range) for distal onset latency, baseline to negative peak amplitude, NCV of tibial motor nerve in males in their 20s were 4.3 ms (3.1–5.4 ms), 7.1 mV (3.4–10.9 mV), and 50.7 m/s (42.2–59.3 m/s), respectively; sural sensory nerve baseline to negative peak amplitude in males in their 20s was 21.7 μV (8.3–35.2 μV). Including the aforementioned data, we present a vast dataset of normative mean values and expanded uncertainties for NCSs of the leg in a healthy Korean population. Furthermore, upper limits for normal side-to-side differences for onset latency, amplitude, and NCV of each nerve are suggested. Conclusion To our knowledge, this is the first study to present the reference standards of leg NCSs with consideration for multifactorial uncertainties in an Asian population. We expect these results to help practitioners make reliable and reproducible clinical decisions.